Handling structural break points in NEMO - Erling Motzfeldt Kravik; Kenneth Sæterhagen Paulsen (Norges Bank, 2020)
This paper documents a new feature in Norges Bank's policy model NEMO, namely the ability to handle structural break points, i.e. shifts in one or more parameter values at a specific point in time. This property is introduced to enable the model to answer new policy-relevant questions, such as the effect of changes in the inflation target and the effect of a sudden drop in the expected long-term oil price. We document the theoretical solution technique and illustrate its usage through a practical example. Additionally, we present a procedure for estimating break points. Our results indicate that including structural shifts is important when interpreting data. Neglecting structural shifts can lead to wrong interpretations of history, which, potentially, could also affect forecast performance.
hdl:11250/2655713
Keywords: 330; Geldpolitik; DSGE-Modell; Prognoseverfahren; Strukturbruch; Norwegen